ANALISIS PERMINTAAN TAMAN HUTAN RAYA SULTAN SYARIF HASYIM KECAMATAN MINAS KABUPATEN SIAK DENGAN METODE BIAYA PERJALANAN (TRAVEL COST METHOD) - Joko Suprianto; Eriyati Eriyati; Ando Fahda Aulia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims To find out the demand for Sultan Syarif Hasyim Rain Park Forest in Subdistrict Minas District Siak Regency as well as factors that affect the demand for travel with travel costs (Travel Cost Method). In this study the population of this study is all visitors Sultan Syarif Hasyim Rain Park Forest in year 2016 is a number of 13,234 visitors. The technique of determining the sample by accidental sampling technique To determine the number of samples from the number of visitors by using the formula calculation Taroyamane error rate of 10% sample of 100 samples. The analytical method used is descriptive quantitative by using multiple linear regression analysis tool.Based on the results of the study note that with the travel costs incurred ranging between Rp45,000 - Rp 350,000 will get the request of Sultan Syarif Hasyim Rain Park Forest between 1 to 5 times. Furthermore, from the calculations that have been done is known that the income has a positive relationship to the number of tourist visits with a significant level of 99%. For the travel cost variable is known to have a negative relationship with the number of tourist visits with a significant level of 99%. While for the travel time variable have negative relation to the number of tourist visit but do not have influence to the number of tourist visit at Sultan Syarif Hasyim Rain Park Forest with a significant level of 90%.Keywords : Request, Travel Cost, Income, Travel Time, S.S.H Rain Park Forest